2024
DOI: 10.7759/cureus.54490
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Platelet Indices as Prognostic Markers of Sepsis: A Medical Intensive Care Unit-Based Cross-Sectional Study at a Rural Setup

Anusha Gupta,
Sunil Kumar,
Sourya Acharya
et al.

Abstract: Introduction Even after the breakthrough advancements in the management and prognostic scoring of sepsis, it remains an important cause of morbidity and mortality encountered in intensive care units (ICUs) throughout the globe. This study highlights the utility of platelet indices as prognostic markers of sepsis. Methods In the present prospective cross-sectional study, a total of 177 patients with sepsis were enrolled using the Sepsis-3 criteria. The platelet indices were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Another study indicated that the mean of non-survivors was substantially higher in MPV and PDW, while PCT did not differ between survivors and non-survivors [33]. According to Gupta et al, non-survivors had MPV that was significantly greater than survivors [43]. A substantial association between MPV and Acute Physiology and Chronic Health Evaluation (APACHE) score, a grading system, indicated that the mean of non-survivors was substantially higher.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that the mean of non-survivors was substantially higher in MPV and PDW, while PCT did not differ between survivors and non-survivors [33]. According to Gupta et al, non-survivors had MPV that was significantly greater than survivors [43]. A substantial association between MPV and Acute Physiology and Chronic Health Evaluation (APACHE) score, a grading system, indicated that the mean of non-survivors was substantially higher.…”
Section: Discussionmentioning
confidence: 99%